2023
DOI: 10.1039/d3tb01490h
|View full text |Cite
|
Sign up to set email alerts
|

Different drug loading methods and antibiotic structure modulate the efficacy of polydopamine nanoparticles as drug nanocarriers

Meera Patel,
Nesha May O. Andoy,
Susannah Megan Tran
et al.

Abstract: The inefficient delivery of antimicrobials to their target is a significant factor contributing to antibiotic resistance. As such, smart nanomaterials that respond to external stimuli is extensively explored for precise...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Loading drugs can occur either during the synthesis process of PDA or as a separate post-synthetic step, and the drug release can be stimulated by laser irradiation, or it may follow a passive route. In this way, PDA can be tailored, in its synthesis and properties, to be a drug delivery system [ 76 ]. It was shown that the encapsulation efficacy of Ce6 in mesoporous PDA nanoparticles reached around 69.64% [ 77 ].…”
Section: Polymeric Nanoparticles With Intrinsic Activity: Enhancing P...mentioning
confidence: 99%
“…Loading drugs can occur either during the synthesis process of PDA or as a separate post-synthetic step, and the drug release can be stimulated by laser irradiation, or it may follow a passive route. In this way, PDA can be tailored, in its synthesis and properties, to be a drug delivery system [ 76 ]. It was shown that the encapsulation efficacy of Ce6 in mesoporous PDA nanoparticles reached around 69.64% [ 77 ].…”
Section: Polymeric Nanoparticles With Intrinsic Activity: Enhancing P...mentioning
confidence: 99%